2014
DOI: 10.1371/journal.pone.0083795
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Admission to a Dedicated Geriatric Unit Decreases Mortality in Elderly Patients with Hip Fracture

Abstract: BackgroundElderly patients with hip fracture have a 5 to 8 fold increased risk of death during the months following surgery. We tested the hypothesis that early geriatric management of these patients focused on co-morbidities and rehabilitation improved long term mortality.Methods and FindingsIn a cohort study over a 6 year period, we compared patients aged >70 years with hip fracture admitted to orthopedic versus geriatric departments in a time series analysis corresponding to the creation of a dedicated geri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 36 publications
3
142
0
7
Order By: Relevance
“…One study was a level 1 prospective randomized control trial [70], and the remaining seven were level 3 studies with historical controls [5,17,24,28,39,40,52]. Results of our metaanalysis showed an average reduction in length of stay by 2.28 days (95% CI, 2.00-2.56 days) (Fig.…”
Section: Complication Rates and Length Of Staymentioning
confidence: 86%
See 3 more Smart Citations
“…One study was a level 1 prospective randomized control trial [70], and the remaining seven were level 3 studies with historical controls [5,17,24,28,39,40,52]. Results of our metaanalysis showed an average reduction in length of stay by 2.28 days (95% CI, 2.00-2.56 days) (Fig.…”
Section: Complication Rates and Length Of Staymentioning
confidence: 86%
“…Additionally, although a few studies have reported improved readmission rates with comanagement [5,39], others have reported no change [17,24,28,52]. We chose not to include a decreased readmission rate in our analysis, although a decreased rate would decrease the costs seen in the comanagement strategy and make it even more favorable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, specific geriatric ICUs are scarce [17], and most VOPs are never visited by a geriatrician. Geriatricians' involvement is an advantage that recently has been found to provide a survival benefit in many other groups [18]. This benefit may reflect the more holistic approach a geriatrician may have to the VOP, leading to better decision-making.…”
Section: Organisationmentioning
confidence: 99%